Yeast screening system reveals the inhibitory mechanism of cancer cell proliferation by benzyl isothiocyanate through down-regulation of Mis12 - Abe-Kanoh, Naomi (Sci Rep, 2019)
Benzyl isothiocyanate (BITC) is a naturally-occurring isothiocyanate derived from cruciferous vegetables. BITC has been reported to inhibit the proliferation of various cancer cells, which is believed to be important for the inhibition of tumorigenesis. However, the detailed mechanisms of action remain unclear. In this study, we employed a budding yeast Saccharomyces cerevisiae as a model organism for screening. Twelve genes including MTW1 were identified as the overexpression suppressors for the antiproliferative effect of BITC using the genome-wide multi-copy plasmid collection for S. cerevisiae. Overexpression of the kinetochore protein Mtw1 counteracts the antiproliferative effect of BITC in yeast. The inhibitory effect of BITC on the proliferation of human colon cancer HCT-116 cells was consistently suppressed by the overexpression of Mis12, a human orthologue of Mtw1, and enhanced by the knockdown of Mis12. We also found that BITC increased the phosphorylated and ubiquitinated Mis12 level with consequent reduction of Mis12, suggesting that BITC degrades Mis12 through an ubiquitin-proteasome system. Furthermore, cell cycle analysis showed that the change in the Mis12 level affected the cell cycle distribution and the sensitivity to the BITC-induced apoptosis. These results provide evidence that BITC suppresses cell proliferation through the post-transcriptional regulation of the kinetochore protein Mis12.